Assessment of housing adequacy towards flood resilience in the municipality of Plaridel, Quezon Province, Philippines - Mazanhi, Patience; Liwag, Carmelita Rosario Eva U. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2025)
Flooding has plagued the world since time immemorial, and it has left much devastation in its wake. Among these, is the displacement of people from their homes. So far, adequate housing has played a vital role in mitigating the adverse effects of these disasters, for example, the location of peoples' homes in less vulnerable areas, and the quality of materials used have been known to reduce the impact of flooding on homes.

Although adequate housing appears to be inextricably linked with the concept of disaster mitigation and resilience, research has been meager at best in establishing this link, hence opening up a gap that requires dire attention, especially in the current climate change crisis. This begs the question, how does housing adequacy influence disaster resilience? The study explores how housing adequacy plays a key role in ensuring flood resilience in Plaridel, a coastal municipality in Quezon Province, Philippines. It assumes that communities with access to adequate housing are more resilient to flooding. Findings show that adequate housing features such as foundations, roofing, walls and supportive initiatives go a long way in enhancing household flood resilience even when the location is classified as vulnerable. Housing adequacy in the municipality fairly meets the standards giving rise to the need to further enhance resilience as it is the most affected by flood disasters. Efforts to ensure adequate housing for flood resilience are still minimal. Most households lack the financial capacity to ensure adequate housing, hence, they continue to suffer from frequent flood occurrences. The study recommends community fundraising initiatives and support systems to cooperatively construct resilient housing. A prioritization of housing in flood resilient efforts by LGUs has the potential to reduce community vulnerability and enhance their resilience.
Thesis
Keywords: Risk Management -- Philippines -- Plaridel (Quezon Province).; Housing -- Philippines -- Plaridel (Quezon Province).; Flood control -- Philippines -- Plaridel (Quezon Province).